Early Colony Growth of the Stingless Bee Heterotrigona itama After Transfer to Cultivation Boxes in Three Types of Anthropogenic Landscapes - Elpe Bibas; Fitriyan Kurnia (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate changes in colony weight during the first ten weeks after transfer to cultivation boxes and to assess nest-external activity (foraging) across mixed-garden, suburban, and urban landscapes. A total of 27 colonies were observed over ten weeks. Colony growth was measured based on changes in colony weight, whereas worker activity was recorded using video observations. The data were analyzed using Linear Mixed Models (LMMs) and Generalized Linear Mixed Models (GLMMs). The results showed that time since placement in the cultivation boxes (LMM: χ² = 17.17; p < 0.001) and its interaction with landscape type (LMM: χ² = 22.13; p < 0.001) had significant effects on changes in colony weight. Colonies in mixed-garden landscapes showed more progressive weight gain, reaching 654.82 ± 81.96 g in week 8 and 737.20 ± 108.37 g in week 10, whereas colonies in suburban and urban landscapes tended to remain stagnant. Landscape type had no significant effect on foraging activity (p > 0.05). In contrast, time had a significant effect on the number of workers carrying nectar (GLMM: χ² = 9.30; p = 0.0023) and resin (GLMM: χ² = 10.23; p = 0.0014). Nectar-carrying activity increased and peaked between weeks 8 and 9, whereas resin-carrying activity was higher during the early weeks and declined in subsequent weeks. Under the specific locations and observation period of this study, mixed-garden landscapes provided more favorable conditions for the early growth of H. itama colonies than suburban and urban landscapes.